The Need of Science Learning to Empower High Order Thinking Skills in 21st Century. Issue 1 (May 2021) - Bahri, A; Jamaluddin, A B; Muharni, A; Fikri, M J N; Arifuddin, M
Abstract: One of the characteristics of 21st century learning is the need to empower higher order thinking skills, especially in science learning. This research is a survey research that aims to determine how the learning process in the field and the desire of students to learn science in empowering higher order thinking skills. Respondents in this study were 102 students of the Faculty of Mathematics and Natural Sciences, The State University of Makassar for the academic year 2019/2020. The instrument used in the instrument sheet was a questionnaire to measure student needs and a deep interview sheet. The results showed that students considered the learning process still negative in its application process. In addition, students also need an innovative learning process that can activate students in the learning process, train critical and creative thinking skills facilitate students to always learn collaboratively, and be able to apply their knowledge in everyday life. Therefore, a solution is needed, namely the development of appropriate learning models in science learning in empowering higher order thinking skills during the learning process.